Rock brittleness evaluation method based on the complete stress-strain curve - ChenYang Liu; Yong Wang; XiaoPei Zhang; LiZhi Du (Fracture and Structural Integrity)
Brittleness plays an important role in the brittle failure process of rocks, and is also one of the important mechanical properties of rocks and a key indicator in rock engineering such as hydraulic fracturing, tunnelling machine borehole drilling and rockburst prediction. Therefore, aiming at the applicability of the brittleness index, this paper summarizes and analyzes the existing brittleness indices based on different experimental methods. Through analysis, it is found that many of the existing methods have their limitations. On the other hand, the brittleness evaluation method based on the stress s-strain curve makes it easier to obtain key parameters and quantify them. Therefore, this paper also adopts this practically widely used method. It proposes a brittleness index based on the post-peak stress drop rate of the rock stress-strain curve and the difficulty of brittle failure, verifies by the traditional triaxial surrounding rock pressure test the accuracy and superiority of BL and further explores the differences between the brittleness indices B8, B11, B12 and BL. Finally, the brittleness index BL and B13 are further contrasted by the existing experimental data.